Should all patients with hyperparathyroidism be screened for a CDC73 mutation?. (8th March 2018) - Bachmeier, Caroline; Patel, Chirag; Kanowski, Peter; Sangla, Kunwarjit
Summary: Primary hyperparathyroidism (PH) is a common endocrine abnormality and may occur as part of a genetic syndrome. Inactivating mutations of the tumour suppressor gene CDC73 have been identified as accounting for a large percentage of hyperparathyroidism-jaw tumour syndrome (HPT-JT) cases and to a lesser degree account for familial isolated hyperparathyroidism (FIHP) cases. Reports of CDC73 whole gene deletions are exceedingly rare. We report the case of a 39 year-old woman with PH secondary to a parathyroid adenoma associated with a large chromosomal deletion (2.5 Mb) encompassing the entire CDC73 gene detected years after parathyroidectomy. This case highlights the necessity to screen young patients with hyperparathyroidism for an underlying genetic aetiology. It also demonstrates that molecular testing for this disorder should contain techniques that can detect large deletions. Learning points: Necessity of genetic screening for young people with hyperparathyroidism. Importance of screening for large, including whole gene CDC73 deletions. Surveillance for patients with CDC73 gene mutations includes regular calcium and parathyroid hormone levels, dental assessments and imaging for uterine and renal tumours.